2014
DOI: 10.1074/jbc.m113.502344
|View full text |Cite
|
Sign up to set email alerts
|

A Membrane-proximal, C-terminal α-Helix Is Required for Plasma Membrane Localization and Function of the G Protein-coupled Receptor (GPCR) TGR5

Abstract: Background: TGR5 is a G protein-coupled bile acid receptor that modulates the immune response, glucose homeostasis, and liver regeneration. Results: Secondary structure of the receptor C terminus determines plasma membrane trafficking. Conclusion: TGR5 plasma membrane content and responsiveness to extracellular ligands depends on C-terminal ␣-helix formation.Significance: This provides insights into the structure-function relationship of TGR5, which is a potential drug target for metabolic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…In fact, the MFIS-FRET measurements showed no change in FRET properties after TC treatment, an observation that is also supported by literature22. As an indicator of G-protein binding, we successfully proved cAMP increase after ligand treatment in all TGR5 variants, which has also been shown recently94243. We have no evidence that TGR5 oligomerization is affected by ligand treatment and subsequent G-protein coupling.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In fact, the MFIS-FRET measurements showed no change in FRET properties after TC treatment, an observation that is also supported by literature22. As an indicator of G-protein binding, we successfully proved cAMP increase after ligand treatment in all TGR5 variants, which has also been shown recently94243. We have no evidence that TGR5 oligomerization is affected by ligand treatment and subsequent G-protein coupling.…”
Section: Discussionsupporting
confidence: 85%
“…This has just been demonstrated for rhodopsin where disruption of dimerization with small peptides decreased receptor stability44. We recently showed that the loss of α-helicality in the TGR5 C-terminus, which constitutes the major interaction surface in the 1/8 interface, severely impairs TGR5 membrane localization and activity9. One can thus speculate that this influence on membrane localization and activity results from a distorted TGR5 dimerization in the ER.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The membrane proximal C-terminus of GPCRs has been shown to be important for membrane localization of these receptors because it can contain a sorting motif (e.g., the F(X) 6 LL motif). Since the N-terminal part of the C-Terminus of TGR5 contains no known sorting motif, we hypothesize that it must be the secondary structure of the C-terminus that determines TGR5 trafficking [3]. …”
mentioning
confidence: 99%